2021
DOI: 10.3390/app11167629
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Antioxidant Compounds and Pigments from Spirulina (Arthrospira platensis) Assisted by Pulsed Electric Fields and the Binary Mixture of Organic Solvents and Water

Abstract: The application of pulsed electric fields (PEF) is an innovative extraction technology promoting cell membrane electroporation, thus allowing for an efficient recovery, from an energy point of view, of antioxidant compounds (chlorophylls, carotenoids, total phenolic compounds, etc.) from microalgae. Due to its selectivity and high extraction yield, the effects of PEF pre-treatment (3 kV/cm, 100 kJ/kg) combined with supplementary extraction at different times (5–180 min) and with different solvents (ethanol (Et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 44 publications
(56 reference statements)
2
28
0
Order By: Relevance
“…than in untreated material. A higher TPC in the PEF-treated sample in current study was probably related to preservation of thermolabile compounds, due to a shortening of drying time by this non-thermal treatment, and/or a higher extractivity, due to the electroporation phenomenon, as it was reported previously in the literature [ 49 ].…”
Section: Resultssupporting
confidence: 75%
“…than in untreated material. A higher TPC in the PEF-treated sample in current study was probably related to preservation of thermolabile compounds, due to a shortening of drying time by this non-thermal treatment, and/or a higher extractivity, due to the electroporation phenomenon, as it was reported previously in the literature [ 49 ].…”
Section: Resultssupporting
confidence: 75%
“…[ 5 ], and Spirulina spp. [ 9 ]. The phytochemical profiling of cyanobacteria is rather similar to that of medicinal plants and other types of algae; in particular, it is predominately made up of pigments and polyphenols [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thanakkasaranee et al [ 36 ] also reported that the yield of CMCH was also dependent on the concentration of NaOH, MW of chitosan, solvent, and reaction temperature. In addition, the solvent ratio and the processing also affect the yield and antioxidant activities [ 37 ].…”
Section: Resultsmentioning
confidence: 99%